Exploring the Growth of a Junior High School Student’s Mathematical Understanding and Higher-Order Thinking - Efuansyah; Syamsulrizal (Program Studi Pendidikan Matematika Universitas Katolik Santo Agustinus Hippo, 2026)
Mathematical understanding develops dynamically and plays an important role in fostering higher-order thinking skills (HOTS). However, studies using the Pirie–Kieren framework have not consistently examined the relationship between the growth of mathematical understanding and higher-order thinking. This study aims to explore the growth of a junior high school student’s mathematical understanding at Junior High School Number 8 Lubuklinggau, and higher-order thinking within the framework of Pirie-Kieren. This study employed a descriptive exploratory approach involving one eighth-grade student with high mathematical ability, selected purposively. The student completed a System of Linear Equations in Two Variables (SPLDV) task designed based on the Pirie–Kieren layers of understanding. Data were collected through observations, interviews, and documentation, and were analyzed thematically. The results show that the student’s mathematical understanding exhibited growth in a dynamic and nonlinear manner, progressing from primitive knowing to structuring, with recurring folding-back. Along this progression, the student demonstrated higher-order thinking, including recognizing concepts, applying prior knowledge in new contexts, constructing mathematical models, identifying properties, abstracting ideas, reflecting on processes, and connecting concepts. These findings indicate that the growth of mathematical understanding is closely associated with the development of higher-order thinking, suggesting that both evolve simultaneously during the learning process.